Role of 6-amino flavone in attenuating cisplatin induced neurotoxicity via inhibition of p-JNK signaling pathway in post-natal day-7 mice - Latafat Kahkashan Ahmad; Rifat Jahan; Amin Jan; Shahid Ali Shah (Khyber Medical University Journal)
OBJECTIVE:  To investigate the protective role of 6-amino flavone (6-AF) in cisplatin-induced neuro-inflammation in the developing brains of post-natal day-7 (PND-7) mice.